What does Hine-nui-te-pō look like? A case study of oral tradition, myth and literature in Aotearoa New Zealand - Perris, Simon (Waka Kuaka, 2018)
This essay concerns Māui’s famous, canonical encounter, known only from Aotearoa (New Zealand), with one of Māori myth’s most important deities: Hine-nui-(i)-te-pō, ‘Great lady of the night’, queen of the underworld and, some would say, goddess of death. In particular, this essay traces Hine-nui-te-pō’s literary afterlife, focusing on formulaic descriptions oft her physiognomy from Te Rangikāheke’s “Tama a Rangi” (an 1849 manuscript) through to Karen Healey’s young-adult novel Guardian of the Dead (2010) and Barry Powell’s World Myth (2014). After introducing Hine-nui-te-pō and her place in Polynesian myth, I detail the textual history of the standard (and, I would argue, now formulaic) description of Hine-nui-te-pō’s physical form, comprising four recurring attributes: (i) eyes of, or like, greenstone (pounamu), (ii) hair of, or like, sea-kelp, (iii) teeth of, or like, obsidian and (iv) a mouth of, or like that of, a barracouta. First, I present a new transcription and translation of the relevant passage of Te Rangikāheke’s “Tama a Rangi”, taken from a facsimile of the manuscript. Then follows an account of the textual history of this passage, through George Grey’s various publications to Agathe Thornton’s 1992 edition and translation. I argue that subsequent editions and translations of this passage subtly misrepresent Te Rangikāheke’s handwritten Māori text. Next, I survey scholarly and literary receptions of this formulaic description, revealing that descriptions of Hine-nui-te-pō derive from, develop and indeed at times depart from Te Rangikāheke’s text; and that Hine-nui-te-pō has over time become a locus of progressive mythopoesis. On the one hand, she is a multiform from whom uniformity across different texts, genres, authors and languages should not be expected. On the other hand, I conclude, it is vital that we not forget Te Rangikāheke’s important but little-known account.